Mortality and causes of death in patients with Parkinson's disease: a nationwide population-based cohort study - Ryu, Dong-Woo; Han, Kyungdo; Cho, A-Hyun (Frontiers in Neurology, 2023)
Objective Parkinson's disease (PD) is a neurodegenerative disease involving multiple systems that can affect mortality. This study aimed to compare all-cause and cause-specific mortality between people with PD and without PD. Methods This population-based prospective cohort study is based on Korean National Health Insurance Service data. The primary outcome was the hazard ratio (HR) of all-cause and cause-specific mortality for PD from 2010 to 2019. Cox proportional hazards regression was applied to calculate HRs under crude and three adjusted models with epidemiologic variables. Results A total of 8,220 PD patients and 41,100 age- and sex-matched controls without PD were registered. Ten-year mortality was 47.9% in PD patients and 20.3% in non-PD controls. The mortality rate was higher among older and male participants. The leading cause of death in PD was nervous system diseases (38.73%), and 97.1% of those were extrapyramidal and movement disorders, followed by circulatory diseases (15.33%), respiratory diseases (12.56%), and neoplasms (9.7%). PD contributed to an increased risk of all-cause death with an HR of 2.96 (95% CI = 2.84–3.08). HRs of death for PD were 3.07 (95% CI = 2.74–3.45) from respiratory diseases, 1.93 (95% CI = 1.75–2.13) from circulatory diseases, 2.35 (95% CI = 2.00–2.77) from external causes, and 2.69 (95% CI = 2.10–3.43) from infectious diseases. Conclusion These results showed that PD was related to a higher risk of mortality in all ages and sexes. The leading causes of death in PD were nervous, circulatory, respiratory, infectious diseases, and external causes.